Legal Method for Determining the Beginning of the Month of Ramadhan and Other Months According to the Rules of Hisab and Ru’yatul Hilal in Islamic Astronomy - Pramita, Leni (Universitas Islam Sultan Agung, 2023)
Determining the start of the months of Ramadhan and Shawwal in the Hijriyah calendar is similar to determining the start of other months, such as Sha'ban and others. However, determining the start of the months of Ramadhan and Shawwal is of great concern to Muslims because these two months have very special practices for Muslims. Obligatory fasting, which is observed once a year, is observed during the month of Ramadhan. Meanwhile, the Eid al-Fitr holiday, which falls at the beginning of the month of Shawwal, is also an important moment for Muslims. This research aims to determine the general method for determining the beginning of the months of Ramadhan and Shawwal, namely reckoning and Ru’yahul Hilal or ru’yah. The reckoning method is a method used to determine the start of fasting using mathematical and astronomical calculations. Meanwhile, ru’yah is a method of determining the start of Ramadhan and Shawwal based on observations of the moon. With this method, the crescent moon will be observed at sunset with the naked eye or optical aids such as a telescope. This type of research is empirical research and the research specifications in writing this thesis are descriptive which aims to explain the legal determination of the beginning of the month of Ramadhan and other months according to the Hisab & Ru’yahul Hilal method in Islamic Astronomy (Falak). The main data sources used in this research are secondary data in the form of; Primary Legal Materials; Secondary Legal Materials; and Non-Legal Materials (Tertiary). The results of the research show that there is a close relationship and complementary interrelationship in the hisab and Ru’yahul Hilal or ru’yah methods used in each of the major Islamic organizations which are the reference for the Ministry of Religion of the Republic of Indonesia in deciding laws which are an option for the community when there are differences. Because difference is a blessing.